2009
DOI: 10.1097/tp.0b013e3181bbee98
|View full text |Cite
|
Sign up to set email alerts
|

The Human “Treg MLR”: Immune Monitoring for FOXP3+ T Regulatory Cell Generation

Abstract: Background Controversy exists about the conditions effecting the development of FOXP3 expressing T cells and their relevance in transplant recipients. Methods We generated CFSE-labeled CD4+CD25highFOXP3+ cells in MLRs (‘the Treg MLR’), with varying HLA disparities and cell components. Five color flow cytometry and 3H TdR uptakes were the readouts. Results 1) Despite lower Stimulation Indices (SI) than 2 DR-mismatched MLRs, 2 DR-matched MLRs generated >2 fold higher percentages when gating on proliferating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 30 publications
13
72
0
Order By: Relevance
“…The regulatory potential of these cells is such that when a blocking antibody was used to neutralize the activity of the IFNgR during the first stimulation, reducing the number of double-positive cells to that observed after coculture of MSCs and T-cells, transferred cells were still able to inhibit a second stimulation. This phenomenon has also been observed for different types of regulatory cells that could be generated/expanded during a first stimulation (where their effect was not fully appreciable) and then used as inhibitory cells in a second stimulation involving autologous responder cells [46,47]. In support of this hypothesis, we observed that the inhibition of cellular proliferation induced by the transfer of effector cells that were stimulated in the presence of MSCs to a second allogeneic stimulation could be partially reversed by the presence of antibodies blocking the IL-10R.…”
Section: Cd25mentioning
confidence: 88%
“…The regulatory potential of these cells is such that when a blocking antibody was used to neutralize the activity of the IFNgR during the first stimulation, reducing the number of double-positive cells to that observed after coculture of MSCs and T-cells, transferred cells were still able to inhibit a second stimulation. This phenomenon has also been observed for different types of regulatory cells that could be generated/expanded during a first stimulation (where their effect was not fully appreciable) and then used as inhibitory cells in a second stimulation involving autologous responder cells [46,47]. In support of this hypothesis, we observed that the inhibition of cellular proliferation induced by the transfer of effector cells that were stimulated in the presence of MSCs to a second allogeneic stimulation could be partially reversed by the presence of antibodies blocking the IL-10R.…”
Section: Cd25mentioning
confidence: 88%
“…3A and B, both column 4; SI inhibition-three experiments together in Figure 2, Supplemental Digital Content 2, http://links.lww.com/TP/A304) and by recruitment of new autologous CFSE positive CD4 + CD25 High FOXP3 + cells, as described in our initial Treg MLR report (15). CD4 + cells that were CD127 − (resulting in >50% CD25 + and FOXP3 + cells, Table 1 It was also observed in responses to the original two DR-matched (specific) stimulator that the modulator SRL Tregs induced the development of higher levels of new CD4 + CD25 High FOXP3 + cells in the CFSE-labeled responding cells, that is, they recruited additional autologous responding cells to become this phenotype ( Fig.…”
Section: Treg Mlr Inhibition and Allospecific Recruitment By Tac Versmentioning
confidence: 99%
“…Originally, it was predicted that CTLp reflects alloreactivity of class I mismatch, and HTLp reflect alloreactivity of class II mismatch. Levitsky et al reported an evaluation of allogeneic reaction that used Treg (Levitsky, Miller et al 2009). They generated carboxy-fluorescein diacetate succinimidyl ester-labeled CD4 + CD25 high FOXP3 + cells in MLR, which they called "Treg MLR".…”
Section: Prediction Of Acute Gvhd In Mismatched Hsctmentioning
confidence: 99%
“…Frequency of CTLp MHC class I (Hadley et al 1990;Falkenburg et al 1996;Moretta et al 1999) Frequency of HTLp MHC class II (Falkenburg et al 1996;Kircher et al 2004) MLR, modified MLR MHC class II (Tsafrir, Brautbar et al 2000) Treg MLR MHC class II (Levitsky, Miller et al 2009) MLR-ELISPOT for IFN-γ MHC class I and II (MiHA) (Araki, Hirayama et al 2010) Table 3. Detection assay to allogeneic antigen Alloreactivity of NIMA-exposed mice and NIMA-nonexposed mice were evaluated by MLR, and we found quite wider range of reactivity in the former compared with the latter.…”
Section: Target Antigen Referencesmentioning
confidence: 99%